Tradisi Appasa’bi pada Bulan Ramadan dalam Perspektif Hukum Islam (Studi Kasus di Kampung Kacidu Kabupaten Bantaeng) - M. Kasim; Ariesman M.; Sulkifli Sulkifli (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2024)
The study aims to understand the tradition of appasa’bi during the month of Ramadan in Kampung Kacidu, Bantaeng district, from the perspective of Islamic law. This tradition is carried out before, during, and after Ramadan to welcome and be grateful for the holy month. Research uses field research methods with historical, sociological, and normative approaches. Data collection was done through interviews and observations. The results show a long-standing tradition of keeping an eye on the Islamic sharia. People are urged to be careful of religious prohibitions. From the perspective of Islamic law, this tradition is permitted as long as it does not conflict with the Shariah and serves good purposes. Traditional processions include worship, dodol-making, study, and joint prayer. In conclusion, the appasa'bi tradition is an ancestral heritage that remains preserved by promoting Islamic values. Recommendation, the need for socialization relates religious aspects in tradition to the younger generation.